Management Strategy of Padang Old Town as a Heritage Tourist Attraction - Suci Ramadani; Fresti Yuliza (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Kota Tua Padang holds great potential as a cultural heritage tourism destination, with its colonial history, distinctive architecture, and Minangkabau cultural narrative. However, the development of this area still faces challenges such as building damage, ownership issues, and limited infrastructure. This study aims to analyze the current management of Kota Tua Padang as a cultural heritage tourism destination, identify obstacles to implementing development strategies, and provide recommendations based on field findings. The research method used a qualitative descriptive approach, with primary data obtained through field observations and semi-structured interviews with managers, government officials, business actors, and local residents, as well as secondary data from official documents, journals, and related literature. This study is based on Steiner's Strategic Management Theory (1979) because the focus of the research is on the analysis of management strategies, implementation, and evaluation of the development of Kota Tua Padang as a cultural heritage tourism destination. The results show that government strategies through physical revitalization programs, creative economy activation, and the pentahelix approach have improved the area's aesthetics. However, gaps remain with actual conditions on the ground, such as lack of long-term maintenance, obstacles to building ownership, irregular spatial planning, limited infrastructure, low community participation, limited funding, and destination competition. The study concludes that the development strategy for Kota Tua Padang is reactive and visionary, with significant potential for a sustainable tourism ecosystem. However, it requires intensified synergy between policymakers, the community, and business actors. This includes revitalization, strengthening, resolving ownership issues, improving infrastructure, raising public awareness, pentahelix collaboration, managing funds, and distinguishing from competition to support collaborative and history-oriented development. This research contributes to the management of urban cultural heritage by the government, business actors, and academics.